Joan of Arc: By Herself and Her Witnesses - Pernoud, Regine (Globe Trade, 1990)
Using historical documents and translated by Régine Pernoud, Joan of Arc seeks to answer the questions asked by Joan's contemporaries as well as us: Who was she? Whence came she? What had been her life and exploits? First published in the United States in 1966 by Stein and Day, this book reveals the historical Joan, described in contemporary documents by her allies as well as her enemies.